Incomplete right bundle branch block and vital capacity. - Sparros, L D (1976)
Right bundle branch block (RBBB) is occasionally encountered in young persons who lack any other evidence of overt cardiac disease (Hiss and Lamb, 1962; Lancaster, Schechter, and Massing, 1972). The block may be complete or incomplete, the latter being more common. Right bundle branch block has been studied in relation to body weight, obesity, serum cholesterol and glucose levels, and blood pressure, but the results have been negative (Ostrander, 1964; Kannel et al., 1962). Data presented here suggest that incomplete RBBB is related to vital capacity.